Resiliency of Silica Export Signatures When Low Order Streams Are Subject to Storm Events. Issue 5 (23rd May 2022) - Fernandez, N. M.; Bouchez, J.; Derry, L. A.; Chorover, J.; Gaillardet, J.; Giesbrecht, I.; Fries, D.; Druhan, J. L.
Abstract: Silicon stable isotope ratios ( δ $δ $ 30 Si) of over 150 stream water samples were measured during seven storm events in six small critical zone observatory (CZO) catchments spanning a wide range in climate (sub‐humid to wet, tropical) and lithology (granite, volcanic, and mixed sedimentary). Here we report a cross‐site analysis of this dataset to gain insight into stream δ $δ $ 30 Si variability across low‐order catchments and to identify potential climate (i.e., runoff), hydrologic, lithologic, and biogeochemical controls on observed stream Si chemical and isotopic signatures. Event‐based δ $δ $ 30 Si exhibit variability both within and across sites (−0.22‰ to +2.27‰) on the scale of what is observed globally in both small catchments and large rivers. Notably, each site shows distinct δ $δ $ 30 Si signatures that are preserved even after normalization for bedrock composition. Successful characterization of observed cross‐site behavior requires the merging of two distinct frameworks in a novel combined model describing both non‐uniform fluid transit time distributions and multiple fractionating pathways in application to low‐order catchments. The combined model reveals that site‐specific architecture (i.e., biogeochemical reaction pathways and hydrologic routing) regulates stream silicon export signatures even when subject to extreme precipitation events. Plain Language Summary: Periods of intense infiltration in the form of rainfall (storm events) or snowmelt push large volumes of dilute fluid through catchments, resulting in evacuation of dissolved solutes derived from weathering reactions. These events occur over short (daily or weekly) timescales, but these pulses of solutes released into small streams can represent a majority of total annual mass flux (from 40% to 70%). Despite their importance, storm events remain largely underrepresented in studies of weathering in watersheds due to challenges in obtaining high frequency measurements. Yet extreme events are expected to become more frequent in the future in response to a changing climate. In this study, we evaluate the dependence of weathering‐derived solute export on hydrology and biogeochemical cycling through measurements of dissolved silicon and silicon stable isotope ratios of stream waters collected during seven significant infiltration events in six small catchments spanning different bedrock lithology and climates. Each catchment was found to have unique silicon chemical and isotopic export signatures reflecting site‐specific subsurface water routing and combination of biogeochemical reactions. These signatures were found to be preserved despite the perturbation exerted by such enhanced infiltration and discharge. In this sense, catchments exhibit resilience, bending but not ceding to strong hydrologic forcing. Key Points: Silicon isotope ratios of storm events within small catchments demonstrate site‐specific biogeochemical and hydrological signatures Cross‐site behavior was successfully described using a model combining fluid transit time distributions and multiple fractionation pathways Site‐specific critical zone architecture remains the main control over stream silicon export signatures even under extreme precipitation conditions